Who Gets to Survive the Apocalypse? Disability Hierarchy in Post-Disaster Fiction in Australian YA. - Kavanagh-Ryan, Kit (Australian Literary Studies)
The article discusses disability hierarchy in post-disaster fiction in Australian young adult. It discusses books like "Interrogation of Ashala Wolf" and "The Foretelling of Georgie Spider" by Ambelin Kwaymullina. It focuses on post-disaster disability and imagines a post-apocalyptic world where children born with paranormal abilities are segregated from the rest of society.